Time to get emotional: determinants of university students’ intention to return to rural areas - Simões, Francisco; Rocca, Antonella; Rocha, Rui; Mateus, Carlos; Marta, Elena; Tosun, Jale (Sustainability, 2021)
The social sustainability of rural areas is affected by the phenomenon of “brain drain” due to younger generations’ outward migration. Our study examines how structural and subjective factors determine the returning intentions of university students over time, before completion of their studies. We conducted a longitudinal, 3-wave survey between 2018 and 2020, involving 349 students (Mean age = 21.89; 63.04% women) and originating from a rural, remote region of Portugal. Using a Tobit panel model approach for data analysis, we found that participants whose mothers had a university degree, who expected higher income 3 years after studies completion, and who were more attached to the place where they were studying were less inclined to return to their native rural area. Conversely, those who were more attached to their rural origins were more likely to show an increased interest in returning over time. Our findings show that university students originating from rural areas and their returning intentions are affected by both structural and subjective factors, in a context of increasing individualisation of mobility intentions and decision making. Consequently, decision makers must start to include the sustained promotion of youths’ emotional bonds to rural areas as a vector of education policy packages in order to combat rural brain drain.
Gesehen am 25.06.2021